Measurement of Percentage Depth Dose using Fabricated Water Phantom Tank for 6 MV Photon Beam - Alssnusi, A. M.; Abdulla, Y. A.; Hussein, N. A.; El-Tashani, F. H. A. (National Research and Innovation Agency, 2025)
Radiotherapy phantoms are utilized to estimate radiation dose delivered to patients, and to improve the accuracy and measurement of radiation dosimetry. The aim of this research is to measure the percentage depth dose (PDD) using a locally designed and fabricated water phantom tank as a cost-effective alternative to the commercially available water phantom used for calibrating therapeutic radiation doses from a linear accelerator. Acrylic material was used to construct the 30 × 40 × 30 cm3 water tank, and tests were conducted on the fabricated phantom using the Elekta linear accelerator at the National Cancer Center Benghazi (NCCB). An IBA FC65-P ionization chamber was used to measure the dose at depths ranging from 0 to 16 cm in 1 cm intervals for 6 MV photon energy at 10 x 10 cm2 field size, and 100 cm source surface distance (SSD). The results indicated that the dose values obtained from the locally fabricated water phantom closely matched those from the commercially installed water phantom and were consistent with values reported in the literature.